Analysis of Local Wisdom Through Megengan Tradition in Encouraging Economic Activities of Nganjuk Residents in East Java - Masruroh, Siti (Proceedings of Annual Conference for Muslim Scholars, 2024)
This research examines local wisdom through the megengan tradition in encouraging economic activities in Nganjuk, East Java. Megengan, which is a tradition leading up to Ramadan that involves various social and cultural activities, has the potential to support the local economy. This tradition not only fosters social values and local economic practices, but can also enhance Islamic values through cultural engagement. The method used is a qualitative approach with interviews and participatory observation to collect data from the local community. The result of the analysis is that the Megengan tradition not only strengthens cultural identity, but also encourages economic activities through increased demand for local products such as food, vegetables, groceries and others. In addition, participation in Megengan activities can increase small business actors to expand networks and income. This study concludes that local wisdom through traditional practices has an important role in the economic development of communities in Nganjuk.